ALARM PENDETEKSI DINI BANJIR DI DESA JATI SARI LANGKAT MENGGUNAKAN ENERGI PANEL SURYA - Fitria Priyulida; Amila; Mido Sitorus; Alvero Wardana Wendra (Smart Education, 2026)
The flash flood disaster that struck Sumatra in late November 2025, particularly in the provinces of Aceh, North Sumatra, and West Sumatra, was caused by changes in very heavy rainfall. Through an impact program, a device was created to provide early flood warnings using solar panels, which have a remarkable effect during flooding. The final result was a system capable of detecting water level using the HC-SR04 ultrasonic sensor and ESP8266-12E module via telegram and buzzer communication. The system's success rate at several stages included 77% at the alert level, 70% at the warning level, and 0% at the danger level.